EFFICIENCY OF FARMS PARTICIPATED IN THE MEASUREAFFORESTATION OF AGRICULTURAL LAND UNDER RDP 2004-2006AND REMAINING FARMS IN THE YEARS 2004-2013 - Marek Zieliński (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of this paper was comparative assessment of production potential, organization of production, economicefficiency and investment abilities of two group of farms from the same communities that collected data for Polish FarmAccountancy Data Network (FADN) in the years 2004-2013. The first group was farms that participated in the measureAfforestation of agricultural land under RDP 2004-2006 (beneficiary farms), while the second group was remaining farmsthat didn’t participate in this measure in the analyzed period. It was found that beneficiary farms in comparison to remainingfarms characterized smaller utilized agricultural area (UAA) lower share of rented area and higher share of own UAA withthe worst quality of soil. Moreover they had worse technical equipment of labour and lower family farm income. However,beneficiary farms like remaining farms had positive rate of reproduction fixed assets but their scale of investment was lower.